Outcome of relapsed or refractory acute B-lymphoblastic leukemia patients and BCR-ABL-positive blast cell crisis of B-lymphoid lineage with extramedullary disease receiving inotuzumab ozogamicin - Kayser, Sabine; Sartor, Chiara; Luskin, Marlise R.; Webster, Jonathan; Giglio, Fabio; Panitz, Nydia; Brunner, Andrew M.; Fante, Matthias; Lutz, Christoph; Wolff, Daniel; Ho, Anthony Dick; Levis, Mark J.; et al. (Haematologica, 2022)
Acute lymphoblastic leukemia (ALL) can relapse in the extramedullary compartment, with or without medullary involvement. Response to treatment may be individual. We evaluated response to inotuzumab ozogamicin in 31 patients with relapsed/refractory B-ALL with extramedullary disease. Median age was 31 years (range, 19-81). All patients were heavily pretreated, including allogeneic hematopoietic stem cell transplantation (HSCT; n=18). Overall response rate after two cycles of inotuzumab ozogamicin was 84% (complete remission, 55%; partial remission, 29%; resistant disease, 13%; early death, 3%). The median follow-up was 29 months and median overall survival was 12.8 months. One-year and 2-year overall survival rates were 53% (95% CI: 37-76%) and 18% (95% CI: 8-43%), respectively. Age had no impact on overall survival when assessed as a continuous variable or dichotomized at 60 years. Twelve patients proceeded to allogeneic HSCT (complete remission, n=6; partial remission, n=3; resistant disease, n=3). Prior to allogeneic HSCT, eight patients received two or fewer cycles and four patients received three or four cycles of inotuzumab ozogamicin. Sinusoidal obstruction syndrome was reported in three patients, including one after transplantation. Allogeneic HSCT, evaluated as a time-dependent variable, had no impact on overall survival. Inotuzumab ozogamicin seems to be effective as a debulking strategy in relapsed/refractory ALL with extramedullary disease. However, inotuzumab ozogamicin followed by allogeneic HSCT seems not to be effective in maintaining long-term disease control.
Gesehen am 09.05.2023